KETAHANAN PANGAN DI GAZA DAN RESPONS INTERNASIONAL: STUDI PERAN INDONESIA DALAM BANTUAN KEMANUSIAAN - Mitta Diahalwani; Rika Sartika (CV. ADIBA AISHA AMIRA, 2025)
Food security in Gaza has become a growing issue exacerbated by prolonged conflict, leading to extreme hunger, malnutrition, and stunting among children. This study aims to analyze the impact of the food security crisis in Gaza and international responses, with a particular focus on Indonesia's role in humanitarian assistance. Based on ten reviewed studies, it is found that severe food insecurity in Gaza is caused by the destruction of food infrastructure and the negative impact of war on the local economy. Several countries, including Indonesia, have actively contributed humanitarian aid; however, logistical and political challenges hinder effective distribution. Therefore, an integrated approach is needed to improve food security in Gaza through diplomacy, direct aid, and sustainable development.